VET Data Report Germany 2012 : facts and analyses accompanying the Federal report on vocational education and training - selected findings - Friedrich, Michael [Herausgeber]; Hanf, Georg [Herausgeber] (Bundesinstitut für Berufsbildung, 2013)
"This English version of the 2012 Data Report provides a selection of the main findings. The first two chapters present the current situation in initial vocational training and in continuing vocational training as well as highlighting the changes which have taken place over the course of time. Chapter 3 ('In focus') is on the different forms of transition from school into VET and is looking at the future of the 'transition system'. This theme is also addressed in the fourth chapter comparing the German situation to the situation in other European countries. The chapter finishes with data on moblity as part of VET." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.3.1 Ausbildung im Dualen System; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.3.3.3 Mobilität; I 2.2 Europa; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Ausbildungsstellenmarkt; Berufseinmündung; Erste Schwelle; Mobilität; Indikatoren; Europa